Navigating Radical Indeterminacy in The Struggle for A Global Collective Consciousness: The Question of Eco-Justice and Law or Universalize the Pluriverse: A Manifesto, More or Less - Auf, Omar (AUC Knowledge Fountain, 2026)
The processes of interpretation, communication, and re-interpretation leads to the emergence of an approximated collective consciousness, for which it may be struggled and contested by hegemonic. The dominant forces of this contest, capitalism and nationalism, lead to an interdivided world: one that possesses the tools to empathize with each other but is instead leading people to keep their heads down and focus on surviving their own contexts, perceived as existing within different historical times on the same timeline. This leads to legal and justice systems that fail their claim to universality and/or impartiality. Incorporating an ecological lens to justice within the framework of political ontology’s pluriverse would render it a highly relational affair, with an emphasis on dialogue between individuals and communities. Taken to the arena of degrowth as one radical approach that may be operationalized within the pluriverse, pluriversal eco-justice may lean on the ethics of care as a relational jurisprudential foundation for lawmaking that is conducive to healthy environmentalism. Ultimately, I argue for adopting political ontology as a practice, collective consciousness as an analytical framework, and eco- justice concerns and approaches as its subject, using degrowth as a concluding case study with the aim of bringing together cross-cutting scholarships that can be utilized in the struggle to avoid ecological collapse. By bringing these threads together I hope to begin the process of laying the groundwork to build an intellectual foundation for an alliance between degrowth advocates, pluversalists, difference feminists, eco-justice scholars, and, broadly, critical theorists interested in ecological issues.